(untitled) (Journal of Agriculture & Rural Development, 2010)
A study was conducted at Postharvest Technology Section, Horticulture Research Centre (HRC) under Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during October 2007 to December 2008 to find a suitable variety for preparation of quality banana chips and their good packaging. Three banana varieties viz. Sabri, BARI Kola-1 and BARI Kola-2 and three packaging materials viz. low density polyethylene, medium density polyethylene and metalex foil pouch were selected for this. The fresh pulps of banana were analyzed for its nutritional composition like moisture content, protein, fat, reducing sugar, non- reducing sugar and total sugar. Based on taste testing panel, freshly prepared chips from Sabri kola scored first for its colour. For crispiness, BARI Kola-2 obtained the lowest score while Sabri and BARI Kola-1 showed the same score. There was no statistically difference for taste, flavour and overall acceptability of the products. Key words: Banana chips, oil content, moisture content, packaging, sensory evaluation. DOI: 10.3329/jard.v7i1.4425 J Agric Rural Dev 7(1&2), 81-86, June 2009